Numerical Study of a Helical Heat Exchanger for Wort Cooling in the Artisanal Beer Production Process - Toapanta-Ramos, Fernando; González-Rojas, Luis; Calero, Elmo; Calderón, Bryan; Quitiaquez, William (Universidad Pedagógica y Tecnológica de Colombia, 2020)
The objective of the present work is to study the behavior of a helical tube and shell heat exchanger, for the cooling of the wort in the process of making craft beer with cold water, through the methodology of computational fluid dynamics (CFD) by finite volume models for heat exchanger modeling. This by using the ANSYS Fluent software, which allows to understand the behavior of the fluid through equations that describe their movement and behavior, using numerical methods and computational techniques. In the mesh convergence, two methods were used, orthogonality and obliquity, with which it was confirmed that the meshing is ideal in the simulations that were carried out. For the simulation, the k-epsilon turbulence model and the energy model were used. Through various simulations, it was obtained that by varying the mass flow, better results are reducing the outlet temperature, with a variation of 15.16 °C, while varying the inlet temperature of the water, there is just a variation from 2.71 °C to 0.01 °C. Therefore, a significant improvement in the performance of the heat exchanger was found. In the same way, it was confirmed that the number of spikes in the heat exchanger is adequate, since the outlet temperature would not be reached with less spikes.